AKUNTABILITAS GURU BK PADA PELAKSANAAN PROGRAM LAYANAN KLASIKAL MELALUI SISTEM EVALUASI PROSES - Yuwono, Dwi (UIN Sunan Kalijaga Yogyakarta, 2023)
The amount of management work makes reports on the program implementation process tend not to be carried out. On the other hand, the demand for accountability of counseling services in schools is increasing. There is an increase in the frequency of technology use in various fields, making all users get used to using it. Guidance and Counseling teachers are no exception in meeting the demands of program management. This study aims to examine the impact of the process evaluation system that has been developed in improving accountability attitudes in counseling programs. The research method used was Explanatory Sequential Design. In the first stage, quantitative measurement was carried out and then analyzed, followed by a qualitative stage and then analyzed. The results of the study showed a 20% change in attitude of the respondents. The biggest factor that causes it is because the system developed has simple features and has outputs that are easy to understand. It is hoped that this research will provide an impetus to the attitude of accountability, especially in the implementation of process evaluation. Keywords: Accountability, Guidance and Counseling, Process Evaluation, Technology.